“REASONABLE MINIMUN" PRINCIPLE IN ELEMENTARY EDUCATION OF CHINA - HE, Lina (Collection of scientific papers «ΛΌГOΣ», 2023)
China's educational aims on providing a solid foundation of education for all students. The Chinese education system places a strong emphasis on equity and ensuring that every child receives a basic level of education that is considered essential. The concept of the "reasonable minimum" as it is emphasises that the country's education system ensures every student to receive a minimum adequate level of education that meets his/her individual needs, abilities and interests in accordance with the national standard of the country. This principle in the Chinese view recognises that not only students have different learning styles, paces and preferences, but also schools have different levels of staffing, different material bases and peculiarities of the educational process organisation due to the presence / absence on this territory of "factors that affect the organisation of education and the regulation of which is under the management of local authorities” [2] (mostly this means a compact residence of representatives of certain national and religious minority).